Crisis management during anaesthesia: vascular access problems. Issue 3 (2nd June 2005) - Singleton, R J; Kinnear, S B; Currie, M; Helps, S C
Abstract : Background: In confronting an evolving crisis, the anaesthetist should consider the vascular catheter as a potential cause, abandoning assumptions that the device has been satisfactorily placed and is functioning correctly. Objectives: To examine the role of a previously described core algorithm "COVER ABCD–A SWIFT CHECK", supplemented by a specific sub-algorithm for vascular access problems, in the management of crises occurring in association with anaesthesia. Methods: The potential performance of a structured approach was evaluated for each of the relevant incidents among the first 4000 reported to the Australian Incident Monitoring Study (AIMS). Results: There were 128 incidents involving problems related to vascular access. The structured approach begins distally, checking the infusion device or fluid (12 incidents), moving proximally by way of the fluid giving line (10), the line deadspace (8), then the catheter/skin interface (65), and on to the peripheral vascular tree (3) and central venous space (23), and finally, the interface of the vascular access system and the attending staff (7). The approach was able to accommodate all the vascular access problems among the first 4000 incidents reported to AIMS. Conclusion: The approach has potential as an easily remembered and applied clinical tool to lead to early resolution of vascular access problems occurring during anaesthesia.